KONTRIBUSI ILMU PENGETAHUAN ISLAM DALAM PEMBENTUKAN KARAKTER UNTUK MENINGKATKAN MUTU PENDIDIKAN - Fadilah, Laili Nur; Istikomah, Nur; Afriantoni, Afriantoni (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
This study, using a literature study method, examines the urgency and implementation of character education in the perspective of contemporary Islamic education. Islamic education strongly emphasizes fundamental moral principles for learners, aiming to form individuals who are moral, responsible, and disciplined according to the noble values ??of Islam. Literature analysis shows a close relationship between morality and science in Islam, where ethics is a guide for the application of science for the benefit. Character education is identified as a crucial component that requires holistic integration in the entire educational process, involving synergy between family, school, and society, in line with the views of Islamic figures such as Al-Ghazali and Ibn Khaldun. This study also highlights that although character education is effective in improving the quality of individuals and education, challenges such as educator readiness, curriculum, and the impact of modernity need to be addressed through a comprehensive strategy. It is concluded that character education is a vital element in developing strong intellectual and moral-spiritual awareness, as well as a potential solution to the moral degradation of society. ABSTRAKPenelitian ini, menggunakan metode studi pustaka, mengkaji urgensi dan implementasi pendidikan karakter dalam perspektif pendidikan Islam kontemporer. Pendidikan Islam sangat menekankan prinsip moral fundamental bagi pembelajar, bertujuan membentuk individu yang bermoral, bertanggung jawab, dan disiplin sesuai nilai-nilai luhur Islam. Analisis pustaka menunjukkan adanya keterkaitan erat antara moralitas dan sains dalam Islam, di mana etika menjadi panduan aplikasi sains demi kemaslahatan. Pendidikan karakter diidentifikasi sebagai komponen krusial yang memerlukan integrasi holistik dalam seluruh proses pendidikan, melibatkan sinergi antara keluarga, sekolah, dan masyarakat, sejalan dengan pandangan tokoh Islam seperti Al-Ghazali dan Ibnu Khaldun. Studi ini juga menyoroti bahwa meskipun pendidikan karakter efektif meningkatkan kualitas individu dan pendidikan, tantangan seperti kesiapan pendidik, kurikulum, dan dampak modernitas perlu diatasi melalui strategi komprehensif. Disimpulkan bahwa pendidikan karakter adalah elemen vital untuk mengembangkan intelektual dan kesadaran moral-spiritual yang kuat, serta solusi potensial bagi degradasi moral masyarakat.